Lipid biomarkers and spectroscopic indices for identifying organic matter sources in aquatic environments: A review. (1st April 2017) - Derrien, Morgane; Yang, Liyang; Hur, Jin
Abstract: Understanding the dynamics of organic matter (OM) and the roles in global and local carbon cycles is challenging to the fields of environmental sciences and biogeochemistry. The accurate identification of OM is an essential element to achieve this goal. Lipids, due to their ubiquitous presence and diagenetic and chemical stability, have long and successfully been used as molecular makers in assessing the sources and the fate of OM in natural environments. In parallel, optical properties of dissolved organic matter (DOM) have been suggested as efficient tools in tracing OM sources. In this review, three representative lipid biomarkers and several common spectroscopic indices were compared for their capabilities to identify OM sources in various aquatic environments. Spectroscopic indices present various benefits in term of the high sensitivity, easy and rapid analysis, and a low cost, providing reliable information on major sources (i.e., autochthonous, allochthonous and anthropogenic) of DOM in given systems investigated. However, for further understanding the associated biogeochemistry (e.g., diagenetic changes in sources), using biomarkers is preferable due to their abilities to identify a wide spectrum of different sources simultaneously as well as their high resolution for mixed OM sources. Thus, a complementary use of both tools is highly recommended for accurately tracking OM sources and the dynamics in aquatic systems, particularly in a watershed affected by multiple sources. Nevertheless, future studies need to be carried out (1) to refine the accuracy of the source assignments in a wide range of settings along with the development of an extensive database encompassing various sources, environmental factors, and geographical locations and (2) to understand how biogeochemical processes reflect the biomarkers and the spectroscopic indices used. Graphical abstract: Highlights: Popularly used lipid biomarkers and spectroscopic indices are compared for source discrimination. Lipid biomarkers are preferable due to the high resolution for mixed organic matter sources. Spectroscopic indices present benefits in terms of sensitivity and rapidity of analysis at low cost. Complementary utilization of both is recommended to overcome limitations of independent use.